THE IMPORTANCE OF SAFFRON MEDICINAL PLANT IN FOLK MEDICINE (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the saffron medicinal plant, its occurrence, history, pharmacological effects and role in folk medicine.